2016
DOI: 10.1055/s-0035-1558331
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and Cytotoxic Isocoumarin Derivatives from an Endophytic Fungus Aspergillus oryzae

Abstract: Oryzaeins A-D (1-4), four new isocoumarin derivatives, along with five known ones (5-9) were isolated from solid cultures of an endophytic fungus Aspergillus oryzae. Their structures were elucidated by detailed spectroscopic analysis and by comparison with reported data of related derivatives. Among them, compounds 1 and 2 represent the first examples of isocoumarins possessing an unusual 2-oxopropyl group and a rare 3-hydroxypropyl group. Compounds 1 and 2 displayed moderate anti-tobacco mosaic virus activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…20 µM. The results revealed that 111 and 112 had moderate anti-TMV potential (inhibition rates 28.4 and 30.6%, respectively) [94]. Antifeedant activities of 134 and 135 were evaluated against larvae of Spodoptera littoralis using glass-fiber discs.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…20 µM. The results revealed that 111 and 112 had moderate anti-TMV potential (inhibition rates 28.4 and 30.6%, respectively) [94]. Antifeedant activities of 134 and 135 were evaluated against larvae of Spodoptera littoralis using glass-fiber discs.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Oryzaeins A ( 156 ) and B ( 157 ) were isolated among metabolites from Aspergillus oryzae, and represented the first example of isocoumarins with an unusual 2-oxopropyl group and a rare 3-hydroxypropyl group. Both compounds displayed moderate antitobacco mosaic viral activities [ 92 ]. Among compounds isolated from Penicillium commune , peniisocoumarin A ( 158 ) and B ( 159 ) are unusual dimeric isocoumarins with a symmetric four-membered core at C-9/9′ and C-10/10′.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental response of these process variables was the production of glucose oxidase (U/ml). Prevalent in other environments such as water (Sessegolo et al, 2011;Oliveira et al, 2016), plants (Pinheiro et al, 2013;Zhou et al, 2016;Corrêa et al, 2014;Russell et al, 2011;Orlandelli et al, 2012), marine organisms (Debbab et al, 2012;Subramani et al, 2013;Hayashi et al, 2016;Cicatiello et al, 2016) and even the glacial arctic environment (Sonjak et al, 2006;Sonjak et al, 2007;Zhang et al, 2016). A fraction of the fungal isolates (20%) were able to produce GOx.…”
Section: Discussionmentioning
confidence: 99%